Impacts of Sustainable Procurement on Organizational Performance - Priscilla Adiao (Uganda Christian University, 2023)
This dissertation consists of five chapters, chapter one consists of introduction of the variables their scopes and statement of the problem, general objectives, specific objectives, research questions and the scope of the study. Chapter two draws down the literature review, chapter three narrates the methods of data collection, population size, study population while chapter four and five crown up with data analysis, discussing research findings, conclusion, recommendations and spot areas for further research. The scope of this study is restricted to the effect of sustainable procurement on organizational performance with specific objectives such as benefits of sustainable procurement, factors affecting sustainable procurement and relationship between sustainable procurement and organizational performance. Some of the benefits of sustainable procurement include; the control of cost through whole life costing, compliance with environmental legislations, management of risks and securing future sustainable suppliers. the factors affecting which are supplier collaboration, customer pressure, competitive advantage, top management support not forgetting the relationship of sustainable procurement and organizational performance that talks about customer expectations being influenced, influence of total costs of ownership of products and services, communication and transparency in fostering, customer preferences for sustainable products and services. The research however was exploratory in nature that is to say it adopted both qualitative and quantitative methods of data collection. In qualitative, the researcher was able to analyze findings on the ground through interactions with the participants at the field in order to make the research more meaningful while in quantitative method the researcher presented the findings statistically in table form, graphs and pie charts. A sample size of 30 respondents was studied of which only 20 responded to the questionnaires. A number of the respondents stated the benefits of sustainable procurement such as control of costs through whole life costing, a good number also agreed that supplier collaboration greatly affects sustainable procurement.it was also discovered that adhering to sustainable certifications and standards based on the respondents as one of the aspects on the relationship of sustainable procurement and organizational performance. The results of the findings with respect to the general and specific objectives of the study; relations were made between the field findings and the literature review to get a good coloration between the two sets of data. She recommended these findings to the students and all procurement practitioners, the organization and finally the government, areas of further research were spotted.
This is a dissertation.